Students as scientists' co-pilots at the onset of technology transfer: a two-way learning process - Ferran Giones; Kari Kleine; Silke Tegtmeier (The Journal of Technology Transfer, 2021)
To provide further knowledge and technology transfer to society, universities are exploring new collaborative models. These new models are regarded as promising alternatives to the patent-centric linear model. However, their implementation requires revising the roles of the actors in the technology transfer process and their relationships. While collaborative models could indeed be an attractive option for universities, there is limited evidence on how these collaboration processes could be effectively introduced. We use a longitudinal embedded multiple case study to explore the contribution of knowledge interactions between scientists and students in the preliminary steps of the technology transfer process. We investigate the learning dynamics between the focal actor, i.e., the scientist, and the students in a university setting to decipher how the introduction of such collaborative processes can contribute to knowledge and technology transfer. Our results suggest that students enrolled in an educational program can contribute to the scientist's interest and engagement in technology transfer. However, we find out that the extent of the students' contribution depends on the shared consensus over the technology function and the openness of the scientist to reconsider the technology's meaning. We contribute to the ongoing exploration of alternative models for technology transfer and the identification of additional roles that students can take in entrepreneurial university ecosystems.
Keywords: I23; L24; O31; O32; 600; Technology transfer models; University; Students; Scientist-student teams